The Importance of Pre-Tournament Psychological Training of Players - Ikramov Amirbek Aminovich; Luqmonov Subhonjon Shavqiddin og‘li (Research Parks Publishers, 2021)
This article highlights the importance of psychological training for athletes in sports games, in particular football, and its impact on result.